Minimizing environmental effects on nutritional needs of growing finishing pigs - David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1987)
Swine have a great ability to grow and reproduce in a variety of environments and facilities. This ability is documented by profitable production in both the most elaborate and the most simple facilities. Efficiency and profitability in environmental extremes are highly variable but performance level during environmental stress is generally less than maximum. The thermal environment strongly influences pig performance with air temperature having the primary effect. All too often, producers fail to consider the total environment of the pig. Air movement, humidity, and, in some instances, solar radiation contribute to how the pig feels. We must consider the total heating or cooling power of the environment. We often refer to this temperature as effective temperature.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine